Response of mineral formulation towards different growth phases of arabica coffee in lowland - Wulanjari, Distiana; Wijaya, Ketut Anom; Rosyady, Muhammad Ghufron; Suwardiyanto, Suwardiyanto; Meliala, Susan Barbara Patricia Sembiring; Setiyono, Setiyono; Farisi, Oria Alit (Jurnal Ilmu Pertanian, 2024)
Arabica coffee cultivation is limited by altitude, which affects its production. Some farmers in Jember Regency are innovating to grow arabica coffee in the lowland, but the potential for leaf rust disease is quite high. Plant natural resistance can be enhanced by adding minerals formulation (containing silica, iodine, and calcium). This research aimed to determine which phase is more effective for applying mineral formulation that induces plant resistance. The formulation was tested on arabica coffee plants grown at the lowland (460 masl) in Jember Regency on 12 years old (y.o) mature and 1 y.o immature plants. One formulation was dissolved in 14 L of water and applied by foliar feeding. The effect was analyzed using two-way T-test of two samples assuming unequal variances at 95% confidence level to determine the differences. The analysis showed that the plants supplemented with the formulation could increase the variables that supported the natural resistance of plants (both mechanically and through the production of chemical compounds), such as polyphenol content, flavonoids, antioxidant activity, total dissolved protein, vitamin C, reducing sugar, lignin, cellulose, hemicellulose, and iodine content in the plant. The response of the formulation application showed that the most resistance variables was better in 1 y.o immature plants than in 12 y.o mature plants. The application of mineral formulation in immature phase will have a better impact on increasing natural resistance, and it has the potential to be used as a supplement for arabica coffee plants cultivated in the lowland.